Reflective Practices for Teacher Education - Kuswandono, Paulus (LLT Journal: A Journal on Language and Language Teaching, 2012)
Studies on reflective practice in teacher education are increasingly getting more attention at least in the last 2 decades. This article discusses concepts of reflection and how it is implemented in educating pre-service teachers on their early stage of professional learning. The purposes of doing the reflection for pre-service teachers are not only for illuminating their professional learning experiences, but also to critically reflect their vocation as teachers, including the values which may be dictated to them through rigid regulations. Reflection in teacher education is crucial as it connects well with learning in that learners use reflection to exercise their mind and to evaluate their learning experiences. Besides, this article also highlights some perceived difficulties to implement reflective practice, as well as ways how to promote reflection.